Video adaptation for stored video delivery over resource-constrained networks - Tao, DaYong (2008)
This project studies content adaptation and bandwidth smoothing techniques for stored video delivery over resource-constrained networks. For the content adaptation approach, we apply the digital item adaptation standard defined in the MPEG-21 multimedia framework to maximize the bandwidth resource utilization and deliver the best quality video given the constraint user environment. The bandwidth smoothing approach presents an optimal frame selection algorithm under limited channel bandwidth and constrained client buffer condition. In addition, a novel reverse frame selection algorithm has been proposed that can find all the optimal frame selection paths for different preloads by running the algorithm just once. We further extend the reverse frame selection algorithm to solve the problem of stored video delivery over bandwidth-limited and time-varying channels.